Spatial smoothing of onshore wind: Implications for strategic development in Scotland. (October 2017) - Commin, Andrew N.; Davidson, Magnus W.H.; Largey, Nicola; Gaffney, Paul P.J.; Braidwood, David W.; Gibb, Stuart W.; McClatchey, John
Abstract: High levels of wind penetration is widely accepted as presenting problems for energy security. With increasing wind deployment this issue is well recognised in Scotland. Spatial smoothing of generation is seen as one method to enhance energy security in a high wind penetration system. This requires wind farms to be developed in a way to take advantage of this smoothing; however, this is not part of the UK/Scottish government wind deployment strategy – which is instead developer led. This research seeks to contribute to a strategic approach to wind development in Scotland, taking into account spatial smoothing – which is shown in this study to be statistically significant within Scotland. Providing quantification of which pre-existing areas of large-scale wind development in Scotland should be the focus of further development and which are of least benefit. Wind farms in southern Scotland offer least in terms of energy security, due to over-concentration of deployment in this area, further development here should be in part considered in terms of export value, rather than utilization within Scotland. The two island areas modelled are shown to have high spatial smoothing value. This work should help inform current political discourse over grid connections to these areas. Highlights: A 30 year hindcast for onshore wind generation in Scotland is created. Areas of wind development of most benefit to generation smoothing are identified. Areas are identified where extra capacity has low value unless primarily for export.